Canadian Arctic Policy and Program Development and Inuit Recognition: A Neoliberal Governmentality Analysis of Canada's Northern Strategy and "The Missing Piece" - Russel, Gail (2015)
In 2007, the Canadian government announced its commitment to the development of the Canadian North through launching Canada's Northern Strategy. The purpose of the Strategy was to address the issue of climate change and its associated effects of increased natural resource extraction and shipping activity in the Canadian Arctic region. Different from past federal government policy and program development initiatives in the Canadian Arctic, this Strategy appeared to make central Inuit voices by way of involving them in the four pillars that constituted the Strategy: Exercising our Arctic sovereignty, promoting social and economic development, protecting our environmental heritage, and improving and devolving northern governance. As the Strategy began to unfold, however, responses from Inuit communities suggested otherwise. Current literature in regards to this issue agrees that Inuit have been placed on the periphery of Canada's Northern Strategy. Instead of asking how this took place, focus has been placed on ways to better insert Inuit voices into the Strategy as it moves forward. As a consequence, this issue does not get fully resolved. My dissertation examines the question: How do Inuit get positioned on the periphery of Canada's Northern Strategy in the first place? I posit that it is in illuminating the political rationale that underpins the Strategy where this question can be addressed. Using a neoliberal governmentality framework, I examine three case studies from Canada's Northern Strategy that are all in their beginning stages of development, in order to reveal how a neoliberal political rationale is operating within each of these projects and, consequently, how it defines the way in which Inuit communities are able to participate. The intention of this analysis is to illuminate both the objective and associated technologies that are responsible for placing Inuit communities on the periphery, in order to be able to reconsider how these aspects influence the Strategy and its relationship with Inuit communities moving forward. Ph.D.